The Listening Public in Public Diplomacy: How Did the Public Respond to President Zelensky on Twitter? - Lassi Rikkonen; Pekka Isotalus (Social Media + Society)
This exploratory study focuses on the public as a listening ensemble that takes part in public diplomacy on Twitter. Here, listening is considered as the receiving component of communication, and responsive behavior as its visible product. The focus is on public communication that followed Russia’s 2022 invasion of Ukraine. A total of 4,392 quote tweets (citing the President of Ukraine Volodymyr Zelensky’s tweets mentioning Ukraine’s possible membership in the European Union) were analyzed using the taxonomy of verbal response modes. Two major modes were identified: responses to the situation by sharing information and persuasion, and responses to Zelensky, Ukrainians, and the public by disclosing feelings and opinions. Interestingly, the different social roles of the public were associated with how much interaction was elicited. The listening public contributes to global deliberativeness; not strictly from an issue-oriented problem-solving perspective, but in the sense that they weave together analytical and social aspects of deliberative reflection.